2018
DOI: 10.1016/j.jbiomech.2018.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Joint contact stresses calculated for acetabular dysplasia patients using discrete element analysis are significantly influenced by the applied gait pattern

Abstract: Gait modifications in acetabular dysplasia patients may influence cartilage contact stress patterns within the hip joint, with serious implications for clinical outcomes and the risk of developing osteoarthritis. The objective of this study was to understand how the gait pattern used to load computational models of dysplastic hips influences computed joint mechanics. Three-dimensional pre- and post-operative hip models of thirty patients previously treated for hip dysplasia with periacetabular osteotomy (PAO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Higher subject-specific loading in S1 increased contact area, while in S2 it increased contact pressure. Although the importance of taking the aberrant gait pattern of dysplasia patients into account when considering contact mechanics has already been reported (Thomas-Aitken et al 2018), the present study indicates that individual gait pattern of healthy subjects is also important. Together, these results highlight complex interplay between geometry, loading and kinematics and their effect on contact mechanics.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Higher subject-specific loading in S1 increased contact area, while in S2 it increased contact pressure. Although the importance of taking the aberrant gait pattern of dysplasia patients into account when considering contact mechanics has already been reported (Thomas-Aitken et al 2018), the present study indicates that individual gait pattern of healthy subjects is also important. Together, these results highlight complex interplay between geometry, loading and kinematics and their effect on contact mechanics.…”
Section: Discussionmentioning
confidence: 53%
“…To the best of our knowledge, only one recent study employed subject-specific boundary conditions, calculated using musculoskeletal models, when considering hip cartilage contact mechanics (Ng et al 2017). Another study used an average dysplastic, but not subject-specific, gait pattern, which altered hip contact stress patterns compared to using a generic gait pattern (Thomas-Aitken et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no similar studies are available on hip contact and muscle forces after THR in DDH patients, indeed this is the first study that analyzed the musculoskeletal loads during gait in DDH patients after THR. Previous research focused on dysplastic hips [32,33] or in patients operated on periacetabular osteotomy [34,35]. Sørensen et al [35] reported a normal hip muscle function during walking after 12 month periacetabular osteotomy, and found that joint force magnitude continued to be higher than normal, justifying this finding with the need for joint structures of a longer time to heal than muscles, with a residual pain alleviating strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous biomechanical studies have shown reduction in contact stresses of the hip joint in patients undergoing PAO and transfer of the load to more medial areas of the acetabulum and femoral head. 26,30 The reduced loads laterally as well as the change in the orientation of the acetabulum likely reduce the continued engagement and edge-loading of the divot lesion.…”
Section: Discussionmentioning
confidence: 99%